Anti-Inflammatory Effects of Kersen Leaf (Muntingia Calabura L.) Ethanol Extract on Wistar Male White Rats - Rahimatul Uthia; Ira Oktaviani Rz; Fathul Jannah; Helmi Arifin; Hengki Afdhal (Poltekkes Kemenkes Riau, 2023)
The research of the effect of ethanol extract of cherry (Muntingia calabura L.) leaf in white male rat has been done. The extract administrated orally by doses 100, 200 and 400 mg/kg BW and negative control group used natrium carboxy methyl cellulose 1%. As positive control group used acetosal 500 mg/kg BW. The inflamation induced by Karagen (1%) injected on the sole of rats. Inflamation volume measured with plestimometer after 7,14 and 21 days administration. The result showed that the Kersen leaf (Muntingia calabura L. ) extract by doses 100, 200 and 400 mg/kg BW can decrease the inflamation volume equal to acetosal 500 mg/kg BW after 21 days.